Power down - Coes, Ben (Coes, Ben. Dewey Andreas novel., 2010)
The first wave of terrorist attacks against America's energy-producing capacity runs afoul of oil rig crew chief Dewey Andreas, a former special forces officer. As Dewey hunts down those responsible for the attacks he comes closer and closer to sleeper agent Alexander Fortuna, who is poised to set off the final assault.